2010
DOI: 10.1248/bpb.33.72
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite 4A, a Synthetic Silicate, Suppresses Melanogenesis through the Degradation of Microphthalmia-Associated Transcription Factor by Extracellular Signal-Regulated Kinase Activation in B16F10 Melanoma Cells

Abstract: In mammals, melanin is the major pigment for the color of human skin and hair. It is synthesized in the melanosomes of melanocytes. This process, called melanogenesis, is a complex phenomenon that occurs in melanocytes by melanogen, cytokine and melanogenic enzymes, such as tyrosinase, tyrosinase-related protein 1 (TRP-1) and tyrosinase-related protein 2 (TRP-2).1) Alpha-melanocyte-stimulating hormone (a-MSH) binds to its specific receptor (MC1R), resulting in activation of GTP-binding protein (Gs), which in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It was previously suggested that inhibition of upregulated tyrosinase enzyme in melanoma cells might inhibit cell proliferation of melanoma cells [42, 43]. This is due to the correlation of microphthalmia-associated transcription factor (MITF) and extracellular signal-regulated kinase (ERK) in the pigmentation, proliferation, and survival of melanocytes and melanoma [23, 26, 35]. Due to this reason, it was expected that the inhibition of MITF expression may also inhibit melanoma cells proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously suggested that inhibition of upregulated tyrosinase enzyme in melanoma cells might inhibit cell proliferation of melanoma cells [42, 43]. This is due to the correlation of microphthalmia-associated transcription factor (MITF) and extracellular signal-regulated kinase (ERK) in the pigmentation, proliferation, and survival of melanocytes and melanoma [23, 26, 35]. Due to this reason, it was expected that the inhibition of MITF expression may also inhibit melanoma cells proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular tyrosinase activity was determined according to the method described by Shin et al [23]. In this method, B16F1 melanoma cells were treated with α -MSH alone and α -MSH with the addition of KA and KA esters at various doses for a total of 72 h incubation.…”
Section: Methodsmentioning
confidence: 99%
“…Pigmentation is one of the most common skin conditions affecting people of all colors and all ages worldwide. In mammals, melanin is the major pigment for the color of human skin and hair, and it is synthesized in the melanosomes of melanocytes [1]. The synthesis of both eumelanin and pheomelanin require melanocyte‐specific enzymes, including tyrosinase, TRP‐1, and Dct.…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosinase activity analysis by zymography. Tyrosinase activity was determined by zymography, as previously described (Shin et al, 2010). After being co-treated with DHMB and IBMX for 72 h, the cells were lysed in PBS (pH 6.8) containing 1% Triton X-100, 1 mM phenylmethanesulfonylfluoride and protease inhibitor cocktail (Sigma, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%